A existência ética e religiosa em Kierkegaard: continuidade ou ruptura? - Sampaio, Laura Cristina Ferreira (2010)
The present study, based on the Kierkegaard s existential dialectics, intends to deal with ethical and religious existence in Kierkegaard, critically assessing the demands of religion and the limits of ethics. Upon establishing the relationship between the ethical and the religious, Kierkegaard using pseudonyms presents varied conceptions. In Fear and Trembling(1843) under the pseudonym Johannes de Silentio, he highlights the rupture between the ethical and the religious, showing that Abraham s story (Gn.22) holds a suspension of ethics; and under the pseudonym Vigilius Haufniensis, in the introduction to Concept of Anxiety (1844), he inserts, into his understanding of ethics, another distinction: between a first ethics , which encompasses Greek ethics as well as Hegel's speculative thinking, and a second ethics , established upon the Christian message, the concept of love to one s neighbor, demanded by a divine commandment, and the principle of ethical life. This second ethics is described a work titled Works of love , authored by way of his own name. In other words, it was attempted to clarify if there was a thorough exclusion or if it would be possible to think of an intrinsic reconciliation, due to some essential relationship between religious existence and ethical existence.